VALIDATION OF A NONINVASIVE METHOD TO ESTIMATE SUBENDOCARDIAL OXYGEN SUPPLY AND DEMAND BALANCE. (June 2022) - Grillo, Andrea; Parati, Gianfranco; Salvi, Lucia; Scalise, Filippo; Tan, Isabella; Sorropago, Antonio; Sorropago, Giovanni; De Censi, Lorenzo; Rovina, Matteo; Fabris, Bruno; Moretti, Francesco; Avolio, Alberto; et al.
Abstract : Objective: Evaluation of balance between subendocardial oxygen supply and demand is useful in order to assess the risk of myocardial ischemia. The subendocardial viability ratio (SEVR, also known as Buckberg index) evaluated by invasive recordings of left ventricular and aortic pressure curves represents a valid method to estimate the degree of myocardial perfusion relative to left ventricular workload. However, routine clinical use of this parameter requires a noninvasive estimation and the demonstration of its reliability. Design and method: Arterial applanation tonometry allows a noninvasive estimation of SEVR as the ratio of the areas directly beneath the central aortic pressure curves obtained during diastole (myocardial oxygen supply) and during systole (myocardial oxygen demand). However, this traditional method does not account for the intraventricular diastolic pressure and proper allocation to systole and diastole of left ventricular isometric contraction and relaxation, respectively, resulting in an overestimation of the SEVR values. These issues are considered in a novel method for SEVR assessment tested in this study. SEVR values were estimated with carotid tonometry by traditional and new method and compared with those evaluated invasively in 51 undergoing an cardiac catheterization for coronary angiography. Results: The traditional method provided significantly higher SEVR values than the reference invasive SEVR: average of differences ± SD = 44 ± 11%. The noninvasive new method showed a much better agreement with the invasive determination of SEVR: average of differences ± SD = 0 ± 8%. The new method for SEVR estimation showed a good repeatability between consecutive assessments (coefficient of variation 7.8%). Conclusions: A noninvasive estimation of SEVR by carotid applanation tonometry is feasible. All the main factors determining myocardial supply and demand flow should be considered in order to provide a valid estimate, in particular intraventricular diastolic pressure, left ventricular isometric contraction and relaxation.